Laparoscopic Treatment of Gallstone Ileus - Huseyin Y. Bircan; Bora Koc; Umit Ozcelik; Ozgur Kemik; Alp Demirag (Clinical Medicine Insights: Case Reports, 2014)
Gallstone ileus is a rare complication of cholelithiasis that has high morbidity and mortality. An intestinal obstruction can be caused by migration of a large gallstone through a biliary enteric fistula or by impaction within the intestinal tract. In this study, we present the case of an 81-year-old woman with a mechanical bowel obstruction by a gallstone that was treated by laparoscopy.